Improving Reflection during Student Teaching with Technology - David S. Allen; Lori Goodson; Dylan Hinrichs (The Advocate, 2016)
​The process of tapping into the power of reflection is a difficult process for many student teachers to accomplish. Multiple factors hinder the process of reflection in novice teachers. Video recorded lessons provide a contextualized focus for reflection on specific pedagogical skills. This study conducted by an undergraduate student during the student internship demonstrates the value of utilized video recorded lesson to assist in the development of one student’s journey toward becoming a reflective practitioner through the use of video recorded teaching episodes.